2010
DOI: 10.1007/s11999-009-1112-3
|View full text |Cite
|
Sign up to set email alerts
|

Gap Balancing versus Measured Resection Technique for Total Knee Arthroplasty

Abstract: Multiple differing surgical techniques are currently utilized to perform total knee arthroplasty (TKA). We compared knee arthroplasties performed using either a measured resection or gap balancing technique to determine if either operative technique provides superior coronal plane stability as measured by assessment of the incidence and magnitude of femoral condylar lift-off. We performed 40 TKA using a measured resection technique (20 PCLretaining and 20 PCL-substituting) and 20 PCL-substituting TKA were impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
208
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(216 citation statements)
references
References 23 publications
2
208
1
5
Order By: Relevance
“…Another difficulty with patient-specific guides is that they do not take into account the effects of soft tissue balancing. The gap-balancing technique has been advocated over the measured resection technique in some studies, including navigation studies, in terms of less abnormal femoral component rotation and coronal instability and better functional outcome [8,10,17,24]. We used the gravity traction method, which uses gravity as a tension force for reproducing a rectangular flexion gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another difficulty with patient-specific guides is that they do not take into account the effects of soft tissue balancing. The gap-balancing technique has been advocated over the measured resection technique in some studies, including navigation studies, in terms of less abnormal femoral component rotation and coronal instability and better functional outcome [8,10,17,24]. We used the gravity traction method, which uses gravity as a tension force for reproducing a rectangular flexion gap.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, currently available patient-specific instruments determine femoral component rotation based on the principle of the measured resection technique without taking individual soft tissue balance into account. This is a potential limitation, as this approach may be more prone to incorrect femoral component rotation and coronal instability compared with the gap-balancing technique [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeons use tensioned gaps in addition to the measured resection to position the implants [11,12]. Postoperative malalignment is reported in a significant number of patients when these conventional instruments are used [4,14,26,35,36].…”
mentioning
confidence: 99%
“…Therefore, the rotation and AP placement of the femoral component are used to create flexion gap symmetry (as opposed to fixed bony landmarks). Multiple comparative studies have demonstrated better femoral component rotation, coronal stability, flexion gap stability, and patellar tracking compared to measured resection techniques [3,7,9]. Sébastien Parratte MD, PhD: I agree with Dr. Springer that instability remains a significant concern with contemporary TKAs.…”
Section: Introductionmentioning
confidence: 94%
“…Research has suggested there is wide variability in femoral component rotation when using bony landmarks, which leads to asymmetry of the flexion space and condylar lift off ( Fig. 1) in flexion [3].…”
Section: Introductionmentioning
confidence: 99%